(untitled) - Wheeler, Anthony J (Upper Saddle River, 2004)
This text covers the most common elements necessary to design, execute, analyze, and document an engineering experiment or measurement system and to specify instrumentation for a production process. In addition to descriptions of common measurement systems, the text covers computerized data acquisition systems, common statistical techniques, experimental uncertainty analysis, and guidelines for planning and documenting experiments
Keywords: Engineering,Experimental design; Experiments